Sociospatial Factors Explaining Daylight Saving Preferences in Australia. Issue 4 (21st September 2021) - Sigler, Thomas; Boyd, Hayley; Kimpton, Anthony
Abstract : The regulation of time and time zones is a fundamentally geographical process that receives surprisingly little scholarly attention. Since the widespread adoption of internationally coordinated time during the industrial revolution, there have been only minor adjustments to the global distribution of time zones, most significantly in the implementation of daylight saving. Conceived as a way to adjust for the relatively longer length of summer daylight hours, the practice of daylight saving involves a twice-yearly shift to account for greater human activity in the evening than during early mornings. Recent developments, however, including increasing urbanization and asynchronous work schedules, have prompted many policymakers to reconsider time zone regulation and, in particular, daylight saving as a mechanism for seasonal adjustment. In this study, we examine sociospatial variables that explain preference for daylight saving in eastern Australia, where acrimonious debates scaffold the political and regulatory basis for its implementation. Focusing on a comparative analysis between Queensland—which does not observe daylight saving—and the remainder of the eastern Australian states and territories—which do observe daylight saving—we take an exploratory approach using inferential statistics to analyze which geographic, socioeconomic, lifestyle, and demographic variables explain a stated preference for daylight saving. We find that geographical and lifestyle variables are most influential in predicting daylight saving preference. With the exception of those north of the Tropic of Capricorn, all groups favor daylight saving, most by a large margin. Set against a local movement to implement daylight saving and a global movement to eliminate it, this study has important findings for time zone policy, suggesting that the logics underpinning such policy should be informed by latitudinal and longitudinal alignment, as well as contemporary lifestyle considerations.